IMPLEMENTASI FUNGSI PENGAWASAN DEWAN PERWAKILAN RAKYAT DAERAH (DPRD) DALAM PELAKSANAAN ANGGARAN PENDAPATAN DAN BELANJA DAERAH (APBD) - Mangonto, Gnadya Christi; Poltak Siringoringo; Marudut Parulian Silitonga (Jurnal Hukum to-ra : Hukum Untuk Mengatur dan Melindungi Masyarakat, 2023)
Many communities in various regions of Indonesia have expressed concerns regarding road construction projects that fail to meet expectations. Roads intended to last five years often deteriorate within just one year after construction, raising public suspicion that infrastructure development is being used as a cover for corrupt practices. This thesis explores two key issues: (1) Whether the oversight function of the DPRD in XXX Regency is implemented effectively and efficiently; and (2) What legal consequences arise when APBD (Regional Revenue and Expenditure Budget) implementation does not align with statutory regulations. The research employs a normative juridical method supported by empirical juridical research through interviews with DPRD members. The findings reveal that the DPRD’s oversight function in XXX Regency aligns with principles of good public governance, particularly transparency. The local government is required to openly manage and disclose financial information since public funds belong to the people. If the APBD is implemented contrary to applicable laws, sanctions will be imposed based on the provisions of the Minister of Finance Regulation regarding the Procedure for Submitting Regional Financial Information, specifically Article 8 paragraphs (1) and (2).